2012
DOI: 10.1002/mus.23356
|View full text |Cite
|
Sign up to set email alerts
|

Passive mechanical properties of the gastrocnemius after spinal cord injury

Abstract: People with ankle contractures after spinal cord injury have stiff gastrocnemius muscle-tendon units. It is not clear whether this reflects changes in properties of muscle fascicles or tendons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…However, several studies have found that the plantar-flexor passive-elasticity in the chronic SCI patients was higher than observed in the healthy age-matched participants. 24,26,46 We speculate that plantar-flexor elasticity in SCI patients increases with immobilization during the acute stage of injury (o1 year), and thereafter, elasticity gradually decreases over time due in part to the muscle atrophy observed in this study. In theory, muscle morphology influences passive tension.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…However, several studies have found that the plantar-flexor passive-elasticity in the chronic SCI patients was higher than observed in the healthy age-matched participants. 24,26,46 We speculate that plantar-flexor elasticity in SCI patients increases with immobilization during the acute stage of injury (o1 year), and thereafter, elasticity gradually decreases over time due in part to the muscle atrophy observed in this study. In theory, muscle morphology influences passive tension.…”
Section: Discussionmentioning
confidence: 70%
“…Theoretically, both muscle and tendon arranged in series can affect the total tissue stiffness, 47 a relationship that has been experimentally confirmed in the plantar-flexors of healthy participants. 17 In contrast, Diong et al 24 observed that the Gas muscle stiffness is increased in SCI participants, whereas Olson et al 6 found that the muscle changes occur at the cell level and reflect muscle fiber transformation from Type I to Type II. In addition, Maganaris 48 showed that patellar tendon CSA, stiffness, and Young's modulus decreased significantly in chronic (18-288 months after injury) complete SCI patients.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…; Diong et al. ). After tracking the image sequence, linear regressions were fitted to the points marking the fascicles and cubic splines were fitted to the points marking the proximal and distal aponeuroses.…”
Section: Methodsmentioning
confidence: 98%
“…The “effective” fascicle length ( l f ; the length of a muscle fascicle projected onto the long axis of the muscle) was calculated from the product of the measured fascicle length and the cosine of the pennation angle (Diong et al. ). All tracking was performed by one investigator.…”
Section: Methodsmentioning
confidence: 99%